PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, FREE CASH FLOW DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG (Perusahaan Manufaktur Sektor Industri Kertas yang Terdaftar di BEI) - Puspitasari, Nurul; Halim, Abdul; Mustikowati, Rita Indah (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2018)
This study aims to examine and explain the effect of managerial ownership, institutional ownership, free cash flow, and company size on debt policy in the paper manufacturing sector companies listed on the Indonesia Stock Exchange in 2010-2015. The type of research used is explanatory research, by testing classic assumptions, and analyzed using multiple linear regression analysis and using the t test for partial testing. The number of samples in this study amounted to 5 companies, and the sampling technique used purposive judgment sampling. This research variable consists of managerial ownership, institutional ownership, free cash flow, company size as an independent variable and debt policy as the dependent variable. The results showed that managerial ownership, free cash flow and company size influence debt policy. While institutional ownership has no effect on debt policy.